Exercise Increases Insulin Content and Basal Secretion in Pancreatic Islets in Type 1 Diabetic Mice - Huang, Han-Hung (Hindawi Publishing Corporation, 2011)
Exercise appears to improve glycemic control for people with type 1 diabetes (T1D). However, the mechanism responsible for this improvement is unknown. We hypothesized that exercise has a direct effect on the insulin-producing islets. Eight-week-old mice were divided into four groups: sedentary diabetic, exercised diabetic, sedentary control, and exercised control. The exercised groups participated in voluntary wheel running for 6 weeks. When compared to the control groups, the islet density, islet diameter, and β-cell proportion per islet were significantly lower in both sedentary and exercised diabetic groups and these alterations were not improved with exercise. The total insulin content and insulin secretion were significantly lower in sedentary diabetics compared to controls. Exercise significantly improved insulin content and insulin secretion in islets in basal conditions. Thus, some improvements in exercise-induced glycemic control in T1D mice may be due to enhancement of insulin content and secretion in islets.